TELAAH STYLE (STILISTIKA) PUISI IDA BAGUS MANTRA DAN PUISI PROF. BAGUS KARYA IDG WINDHU SANCAYA - I Wayan Juliana (Sekolah Tinggi Agama Hindu Negeri Mpu Kuturan Singaraja, 2021)
The figures of Ida Bagus Mantra and Prof. Bagus are two Balinese figures who not only had a major influence on the Faculty of Letters which is now the Faculty of Cultural Sciences but also on Balinese society. His big name until now has served as the name of a vital place in the Faculty of Cultural Sciences. Balinese writer IDG. Windhu Sancaya immortalized and used these two figures as his inspiration in writing poetry. Ida Bagus Mantra's poems and Prof. Bagus's poems are included in the Coffe Shop Poetry collection. This collection of poems led IDG Windhu Sancaya to win the 2003 Literature Rancage Award.In this study, the poetry of Ida Bagus Mantra and Prof. Bagus will be analyzed based on stylistic studies to see the figures of Ida Bagus Mantra and Prof. Bagus. The problem of this study is about the style used by the author in describing the figures of